KOMBINASI MINYAK KULIT JERUK MANIS DAN PEPERMIN SEBAGAI PENGAROMA ALAMI PADA SEDIAAN DEODORAN KRIM: EVALUASI KARAKTERISTIK FISIK DAN IRITASI KULIT - Mayangsari, Fransisca Dita; Elasari Dwi Pratiwi; Muhammad Arendra Ardiansyah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
Sweet orange peel oil (MJ) and peppermint oil (MP) are essential oils. The MJ contained mainly limonene, while the MP contained mainly menthol. These compounds give MJ and MP their distinctive aromas but can also potentially cause skin irritation, especially when used in high concentrations. The purpose of this study was to observe the effect of adding a combination of essential oils (MJ and MP) at a concentration of 3% on the physical characteristics and skin irritation levels of cream deodorants. The ratios of MJ:MP added were 0:0 (F0), 100:0 (FA), 50:50 (FB), and 0:100 (FC). In the physical characteristic test, observations included pH, organoleptic, viscosity, and spreadability. In the irritation test, observations included erythema and edema on the skin of white rat. Based on the organoleptic test, it is known that F0 was odorless, FA had the aroma of MJ, FB had the aroma of MP with a little MJ, and FC had the aroma of MP. All four formulas were white in color and had a semi-solid consistency. They had a pH between 5.27-5.68. The formula with the highest pH was F0. All four formulas had a spreadability value between 5.20-5.53. These values ??were not significantly different. All four formulas had a viscosity value between 14,066-14,980 cP. These values ??were not significantly different. The results of skin irritation observations showed that all formulas had a primary irritation index score of 0. The study concluded that the ratio of MJ and MP affected the aroma and pH of the cream deodorant but did not affect the color, consistency, viscosity, and spreadability. None of the formulas causes skin irritation.